Study of corn kernel breakage susceptibility as a function of its moisture content by using a laboratory grinding method - Ya-nan GUO; Liang-yu HOU; Lu-lu LI; Shang GAO; Jun-feng HOU; Bo MING; Rui-zhi XIE; Jun XUE; Peng HOU; Ke-ru WANG; Shao-kun LI (Journal of Integrative Agriculture, 2022)
The rate of corn kernel breakage in the grain combine harvesters is a crucial factor affecting the quality of the grain shelled in the field. The objective of the present study was to determine the susceptibility of corn kernels to breakage based on the kernel moisture content in order to determine the moisture content that corresponds to the lowest rate of breakage. In addition, we evaluated the resistance to breakage of various corn cultivars. A total of 17 different corn cultivars were planted at two different sowing dates at the Beibuchang Experiment Station, Beijing and the Xinxiang Experiment Station (Henan Province) of the Chinese Academy of Agricultural Sciences. The corn kernel moisture content was systematically monitored and recorded over time, and the breakage rate was measured by using the grinding method. The results for all grain samples from the two experimental stations revealed that the breakage rate y is quadratic in moisture content x, y=0.0796x2−3.3929x+78.779; R2=0.2646, n=512. By fitting to the regression equation, a minimum corn kernel breakage rate of 42.62% was obtained, corresponding to a corn kernel moisture content of 21.31%. Furthermore, in the 90% confidence interval, the corn kernel moisture ranging from 19.7 to 22.3% led to the lowest kernel breakage rate, which was consistent with the corn kernel moisture content allowing the lowest breakage rate of corn kernels shelled in the field with combine grain harvesters. Using the lowest breakage rate as the critical point, the correlation between breakage rate and moisture content was significantly negative for low moisture content but positive for high moisture content. The slope and correlation coefficient of the linear regression equation indicated that high moisture content led to greater sensitivity and correlation between grain breakage and moisture content. At the Beibuchang Experiment Station, the corn cultivars resistant to breakage were Zhengdan 958 (ZD958) and Fengken 139 (FK139), and the corn cultivars non-resistant to breakage were Lianchuang 825 (LC825), Jidan 66 (JD66), Lidan 295 (LD295), and Jingnongke 728 (JNK728). At the Xinxiang Experiment Station, the corn cultivars resistant to breakage were HT1, ZD958 and FK139, and the corn cultivars non-resistant to breakage were ZY8911, DK653 and JNK728. Thus, the breakage classifications of the six corn cultivars were consistent between the two experimental stations. In conclusion, the results suggested that the high stability of the grinding method allowed it to be used to determine the corn kernel breakage rates of different corn cultivars as a function of moisture content, thus facilitating the breeding and screening of breakage-resistant corn.